Pengaruh Kualitas Pelayanan Dan Kepuasan Terhadap Loyalitas Pasien - Solehudin Solehudin; Inas Syabanasyah (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Patient loyalty is often closely related to patient satisfaction with the experience they get during medical treatment. Issues related to service quality, long waiting times, lack of effective communication with patients, or disrespectful attitudes from medical staff can all cause patients to feel dissatisfied and unmotivated to return to the same health facility. This type of quantitative research with a design using correlation analysis, cross sectional. The population in the study were 193 patients treated at a private hospital in Jakarta. The research sample was 130 with the Slovin formula, the sampling technique used quota sampling and the data collection instrument used a questionnaire. Analysis of research data used multiple linear regression. The results showed that service quality partially had a significant effect on patient loyalty with a sig value of 0.036. Partial satisfaction has a significant effect on patient loyalty with a sig value of 0.001 Service quality and satisfaction simultaneously have a significant effect on patient loyalty with a sig value of 0.001 and each effect is 94.1%. In conclusion, the quality of hospital services and patient satisfaction have a significant effect on patient loyalty.. Â